Bioactive Synthetic Peptides for Oral Tissues Regeneration - Bermúdez, Mercedes; Hoz, Lía; Montoya, Gonzalo; Nidome, Mikado; Pérez-Soria, Adriana; Romo, Enrique; Soto-Barreras, Uriel; Garnica-Palazuelos, Julio; Aguilar-Medina, Maribel; Ramos-Payán, Rosalío; Villegas-Mercado, Carlos (Frontiers in Materials, 2021)
Regenerative therapy in oral tissues has gained relevance since tissue loss due to congenital or acquired diseases as well as trauma is a major health problem worldwide. Regeneration depends on the natural capacity of the body and the use of biomaterials and bioactive molecules that can module the processes to replace lost or damaged tissues and restore function. The combined use of scaffolds, cells, and bioactive molecules such as peptides is considered the best approach to achieve tissue regeneration. These peptides can induce diverse cellular processes as they can influence cell behavior and also can modify scaffold properties, giving as a result the enhancement of cell adhesion, proliferation, migration, differentiation, and biomineralization that are required given the complex nature of oral tissues. Specifically, synthetic peptides (SP) have a positive influence on scaffold biocompatibility since in many cases they can mimic the function of a natural peptide or a full-length protein. Besides, they are bioactive molecules easy to produce, process, and modify, and they can be prepared under well-defined and controlled conditions. This review aims to compile the most relevant information regarding advances in SP for dental and periodontal tissue regeneration, their biological effects, and their clinical implications. Even though most of the SP are still under investigation, some of them have been studied in vitro and in vivo with promising results that may lead to preclinical studies. Besides there are SP that have shown their efficacy in clinical trials such as P11-4 for enamel regeneration or caries prevention and ABM/P-15 for cementum, periodontal ligament (PDL), and alveolar bone on a previously calculus- and biofilm-contaminated zone. Also, some SP are commercially available such as PTH1-34 and PepGen P-15 which are used for bone defects treatment. .